Simulation model for the optimization of a radiant plate hot-smoking process. (February 2015) - Raffray, Guilhem; Sebastian, Patrick; Collignan, Antoine
Highlights: A 1D simulation model was built for the optimization of the hot smoking process. The simulation results were consistent with both literature and experimental trials. 8 design variables were related to the process performances of the radiant plate smoker. A thousand of random simulations were used to estimate the computing time and rate of success. A preliminary design solution was found to be more efficient than the current pilot. Abstract: This paper fully describes a simulation model of the radiant-plate hot smoking process, adapted to design optimization. A simulation model from previous work is improved with some features which mainly concern heat and mass transfers, pressure losses, drying air recycling and fish drying behavior. For the purpose of preliminary design, the industrial objectives of product quality, productivity and energy efficiency are mathematically expressed using performance indicators called observation variables. The simulating tool provides low calculation times and high rate of success. Within the domain of design variables, the model predicts the process behavior with coherency.